Photocatalytic hydrogen production performance of 1-D ZnO nanostructures: Role of structural properties. (13th November 2020) - Galdámez-Martínez, A.; Bai, Yang; Santana, G.; Sprick, Reiner Sebastian; Dutt, A.
Abstract: Synthesis of zinc oxide (ZnO) nanowires (NWs) grown via vapor-liquid-solid (VLS) process using Gold (Au) as a catalyst metal on aluminum-doped zinc oxide (AZO) seed layer is reported in the present work. During the growth procedure, the nucleation process helps us to obtain ZnO nanowires with Au on the tip, confirming the VLS growth mechanism. Different morphologies were obtained after the variation in the growth parameters in the VLS process, and further, their role in the photocatalytic performance was studied. Changes in the structural properties of nanowires allowed us to modify the aspect ratio and surface area of the nanostructures. X-ray diffraction (XRD) showed that the principal orientation of the nanowires was (002) in the present case. Scanning electron microscopy (SEM) showed the structural properties of 1-D nanostructures (nanowires), and statistical analysis revealed that the average diameter in the present case was found to be varied from 57 to 85 nm. Scanning transmission electron microscopy (STEM) technique revealed the different elements present on the surface of ZnO NWs. Further, the compositional profile of nanostructures was cross-verified using Energy dispersive Spectroscopy (EDS). Photoluminescence (PL) and UV Visible studies were employed to study the optical properties of nanowires. UV–Vis measurements showed the role of different structural properties of nanowires on the absorption spectra, especially in the visible region. The ZnO nanowires were tested as photocatalysts for hydrogen production from water splitting reaction, and it was found in particular nanowires with random orientation with optimal diameter distribution show the stable and highest photocatalytic performance. Graphical abstract: Photocatalytic hydrogen production of ZnO nanowires grown by VLS technique using gold nanoparticles as metal catalyst nucleation centers. The influence of nanowires with different structural and optical properties over the hydrogen evolution ratio was evaluated. Image 1 Highlights: ZnO nanowires with Au on the tip were grown by a more economical route. The aspect ratio, surface area, and morphology of the nanostructures were varied. Morphologies of nanowires have a vital influence on the absorption parameter. ZnO nanowires with 85 nm showed the highest photocatalytic performance.